Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In Quantum Optics and Quantum Mechanics, the time evolution operator

$$U(t,t_i) = \exp\left[\frac{-i}{\hbar}H(t-t_i)\right]$$

is used quite a lot.

Suppose $t_i =0$ for simplicity, and say the eigenvalue and eigenvectors of the hamiltionian are $\lambda_i, \left|\lambda_i\right>$. Now, nearly every book i have read and in my lecture courses the following result is given with very little or no explanation:

$$U(t,0) = \sum\limits_i \exp\left[-\frac{i}{\hbar}\lambda_it\right]\left|\lambda_i\right>\left<\lambda_i\right|$$

This is quite a logical jump and I can't see where it comes from, could anyone enlighten me?

share|cite|improve this question
up vote 7 down vote accepted

Starting with:

$$U(t,t_i) = e^{\frac{-i}{\hbar }H(t-t_i)}$$

If $t_i=0$:

$$U(t,0) = e^{\frac{-i}{\hbar }Ht}$$

Using the identity: $\sum\limits_i \left|\lambda_i\right>\left<\lambda_i\right|=\mathbb{I}$

$$U(t,0) = \sum\limits_i e^{\frac{-i}{\hbar }Ht}\left|\lambda_i\right>\left<\lambda_i\right|$$

Since the exponential of an operator is (by Taylor expanding): $e^H=\mathbb{I}+H+\frac{1}{2}H^2+\dots$

And: $H\left| \lambda_i \right> =\lambda_i \left| \lambda_i \right>$

You should be able to see that:

$$U(t,0) = \sum\limits_i e^{\frac{-i}{\hbar }\lambda_it}\left|\lambda_i\right>\left<\lambda_i\right|$$

share|cite|improve this answer
I always forget about the series expansion, thanks very much – StickyCube May 18 '13 at 17:06

Without loss of generality, let's take the $|\lambda_i\rangle$ to be orthonormal. Notice that, by the spectral theorem, the hamiltonian can be written as follows: $$ H = \sum_i \lambda_i P_i, \qquad P_i = |\lambda_i\rangle\langle \lambda_i| $$ Each operator $P_i$ is a projectors onto the subspace spanned by $|\lambda_i\rangle$. Notice, in particular, that $$ P_i^2 = P_i, \qquad P_iP_j = P_jP_i = 0 $$ and a mathematical induction argument gives $$ P_i^n = P_i $$ for all $n\geq 1$. Now, for notational simplicity let $$ \mu = -\frac{i}{\hbar}t $$ Then we have $$ U(t,0) = e^{\mu H} = \sum_{n=0}^\infty \frac{1}{n!}\mu^nH^n $$ but notice that using the properties of projection operators written above, we have $$ H^n = \sum_{i_1, \dots, i_n}\lambda_{i_1}\cdots\lambda_{i_n}P_{i_1}\cdots P_{i_n} = \sum_i\lambda_i^nP_i $$ and therefore $$ U(t,0) = \sum_i\sum_n\frac{1}{n!}(\mu\lambda_i)^nP_i = \sum_ie^{\mu\lambda_i}P_i $$ as desired.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.